Treatability of Wastewater Containing Reactive Yellow 145 Dyestuff by Ozonation Process - Pınar Nazire Tanattı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
When the textile industry wastewater volume and considering the composition appears to be one of the most environmentally hazardous industries. Due to the basic properties of textile dyeing industry wastewater, additional precaution are required besides conventional wastewater treatment to remove color. The most basic approach is to remove the color of the wastewater and to break down the chromophores and double bonds that make up the color by oxidative means. In this study, the treatability of wastewater containing Reactive Yellow 145 (RY 145) dyestuff by ozonation process has been investigated. The initial concentration of the wastewater containing RY 145 is 50 mg / L. In the study, pH, O3 dose and reaction time parameters have been studied in RY 145 dye removal. The most appropriate removal of RY 145 from wastewater have occured at pH 5, 0.05 g / L.sa O3 dose and 10 minutes reaction time. The removal efficiency of RY 145 has obtained as 99.07% under optimum conditions.